2017
DOI: 10.1371/journal.pone.0178799
|View full text |Cite
|
Sign up to set email alerts
|

Naïve helper T cells with high CD5 expression have increased calcium signaling

Abstract: The adaptive immune response is orchestrated by T helper cells and their function is dependent upon interactions between the T cell receptor (TCR), peptide MHC (pMHC) and co-receptors. TCR-pMHC interactions initiate calcium signaling cascades which determine T cell activation, survival, proliferation and differentiation. CD5 is a co-receptor that plays an important role in regulating T cell signaling and fate during thymocyte education. CD5 surface expression on mature single positive thymocytes correlates wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Found in T lymphocytes, CD5 is a type of cluster differentiation antigen. High CD5 expression in peripheral T cells allows them to better respond to foreign antigens and enrich memory populations to produce stronger antigenic responses when exposed to the same antigen again (Freitas et al, 2017). Differences in CD5 methylation may lead to a change in the expression of CD5 in the peripheral blood of the CP and DP in this study, which may have had an effect on the immune responses of the two pigs during immunization programs.…”
Section: Dmgs Involved In Immunity and Reproductionmentioning
confidence: 83%
“…Found in T lymphocytes, CD5 is a type of cluster differentiation antigen. High CD5 expression in peripheral T cells allows them to better respond to foreign antigens and enrich memory populations to produce stronger antigenic responses when exposed to the same antigen again (Freitas et al, 2017). Differences in CD5 methylation may lead to a change in the expression of CD5 in the peripheral blood of the CP and DP in this study, which may have had an effect on the immune responses of the two pigs during immunization programs.…”
Section: Dmgs Involved In Immunity and Reproductionmentioning
confidence: 83%
“…In addition, differences in IFNγ production remain evident in activated monoclonal CD5 lo versus CD5 hi CD4 + T cells in response to antigen challenge in vivo . TCR affinity for foreign antigen alone, however, is not the only factor influencing TCR signal strength, and it has previously been shown that the kinetics of cytosolic calcium mobilization in CD5 lo and CD5 hi CD4 + T cells after activation is distinct even when TCR affinity for cognate antigen is identical between the two populations . More recently, it has been suggested that strong basal TCR signals correlate with higher expression of negative regulators of TCR signaling as well as markers of anergy and are associated with attenuated responses to agonist stimulation .…”
Section: Discussionmentioning
confidence: 99%
“…TCR affinity for foreign antigen alone, however, is not the only factor influencing TCR signal strength, and it has previously been shown that the kinetics of cytosolic calcium mobilization in CD5 lo and CD5 hi CD4 + T cells after activation is distinct even when TCR affinity for cognate antigen is identical between the two populations. 28 More recently, it has been suggested that strong basal TCR signals correlate with higher expression of negative regulators of TCR signaling as well as markers of anergy and are associated with attenuated responses to agonist stimulation. 26 Thus, in addition to evidence of cytokine production modulation by CD5 itself, 13,18 there is likely a complex interplay of distinct affinities for foreign antigen, TCR signal modulation, metabolic profiles and cytokine sensitivity, that drive differences in IFNc production potential in CD5 lo and CD5 hi CD4 + T-cell subsets.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CD5 appeared to play an important role in this Ca 2+ mobilization, as the LL056 CD5-deficient T cells showed reduced Ca 2+ responses compared to CD5 sufficient ones. 89 naïve thymocytes from CD5-deficient mice showed enhanced cell death, which correlated with reduced levels of pAKT after stimulation with anti-CD3 + anti-CD28. 62 It has been reported that the PI3K/AKT/mTOR pathway inhibits Tregs generation, and therefore it is possible that the decreased Akt phosphorylation might favor tTreg generation in CD5-deficient mice.…”
Section: Cd5 As a Regulator Of T Cell Anergymentioning
confidence: 96%
“…The enhanced T cell response of LL056 T cells correlated with an increased calcium mobilization at early times after stimulation compared to that observed in LLO118 cells. Moreover, CD5 appeared to play an important role in this Ca 2+ mobilization, as the LL056 CD5‐deficient T cells showed reduced Ca 2+ responses compared to CD5 sufficient ones …”
Section: Cd5 As a Regulator Of T Cell Anergymentioning
confidence: 99%